2016
DOI: 10.1039/c6gc01482h
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of bio-based ionic liquids for the extraction and purification of IgG antibodies

Abstract: In the past decade, remarkable advances in the production and use of antibodies as therapeutic drugs and in research/diagnostic fields have led to their recognition as value-added proteins. These biopharmaceuticals have become increasingly important, reinforcing the current demand for the development of more benign, scalable and cost-effective techniques for their purification. Typical polymer-polymer and polymer-salt aqueous biphasic systems (ABS) have been studied for such a goal; yet, the limited polarity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 61 publications
4
76
1
Order By: Relevance
“…previously applied PPG–IL ABS for the separation of IgG from serum samples. Albeit high recovery yields were reported, the purification percentages were considerably lower than those obtained in this work (< 30%) . Further optimization studies aiming at both the complete partitioning of IgG to the IL‐rich phase and the precipitation of albumin at the interface may be thus envisioned with IL‐based ABS to confirm their potential as alternative purification systems for antibodies.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…previously applied PPG–IL ABS for the separation of IgG from serum samples. Albeit high recovery yields were reported, the purification percentages were considerably lower than those obtained in this work (< 30%) . Further optimization studies aiming at both the complete partitioning of IgG to the IL‐rich phase and the precipitation of albumin at the interface may be thus envisioned with IL‐based ABS to confirm their potential as alternative purification systems for antibodies.…”
Section: Resultsmentioning
confidence: 67%
“…Although the ILTPP approach does not induce the recovery of IgG at the interface, it however allows the precipitation of the major contaminant protein from serum (albumin), leading to an increase in the IgG purity at the IL‐rich phase. Mondal et al . previously applied PPG–IL ABS for the separation of IgG from serum samples.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, polymer/salt‐based ABS using cholinium ([Ch] + )‐based salts (or ionic liquids, ILs) were proposed as platforms for solutes partition, particularly, due to the relative hydrophobicity/hydrophilicity balance between the coexisting phases . Furthermore, it was demonstrated that [Ch] + ‐based salts can promote specific protein‐ions interactions, acting directly on the protein partitioning capacity, as shown for beta‐lactoglobulin, A and B, lysozyme, and ribonuclease A and B, as well as on protein stabilization, as previously observed for monoclonal antibodies, cytochrome c, rubisco, bovine serum albumin (BSA) and α‐chymotrypsin …”
Section: Introductionmentioning
confidence: 65%
“…Recently, polymer/salt-based ABS using cholinium ([Ch] + )-based salts (or ionic liquids, ILs) were proposed as platforms for solutes partition, [22][23][24][25] particularly, due to the relative hydrophobicity/hydrophilicity balance between the coexisting phases. 26 Furthermore, it was demonstrated that [Ch] + -based salts can promote specific protein-ions interactions, acting directly on the protein partitioning capacity, as shown for beta-lactoglobulin, A and B, lysozyme, and ribonuclease A and B, 27 as well as on protein stabilization, 11 as previously observed for monoclonal antibodies, 28 cytochrome c, 24 rubisco, 19 bovine serum albumin (BSA) 29 and -chymotrypsin. 30 These previous studies demonstrated that polymer/salt ABS can provide biocompatible environments to maintain the protein structural conformation 11,19,24,[28][29][30] and to enlarge the range of protein partition driving mechanisms, 27 but a careful selection of the phase forming agents is crucial.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation